A COMPARATIVE ANALYSIS BETWEEN NATURAL-SCIENCE AND SOCIAL-SCIENCE STUDENTS' CRITICAL THINKING IN WRITING ANALYTICAL EXPOSITION TEXT : A Case Study in a Private Senior High School in Bandung - Akmaliyah, Febriyani Nuril (2015)
This study aimed to investigate two things: 1) how different characteristic of natural-science and social-science program affect the students' ability in writing analytical exposition text, and 2) what are the most dominant critical thinking standards in each text of natural-science and social-science students. This study employed by using descriptive qualitative methodology, particularly a case study design. The participants of this study were 6 students, who were categorized as low-achiever, middle-achiever, and high-achiever, from natural-science and social-science programs in a private senior high school in Bandung. The instrument used to collect the data in this study was students' texts analysis. The texts were analyzed in two phases: first, to be analyzed from the linguistic perspective: the purpose, schematic structure and language features of analytical exposition text; then, through critical thinking (CT) perfective using theory of CT to find out to the most dominant CT standards available in students' CT element in writing analytical exposition text in each program. The result of this study indicated that the difference result of writing ability was not affected by different background programs, but different level of achievement (low, middle, high achiever). Moreover, this study also indicated that the most dominant CT standards found in each programs were: clarity in natural-science and clarity and relevance in social-science. Those results, however, was not absolute since it only represented in a small area. Therefore, further comprehensive researches on this subject are strongly suggested to be conducted in the future. Keywords: critical thinking, writing, analytical exposition text, natural-science and social-science program. Penelitian ini bertujuan untuk menganalisis dua hal: 1) bagaimana perbedaan karakteristik antara siswa IPA dan IPS mempengaruhi kemampuan mereka dalam menulis teks eksposisi analitis, serta 2) standar berfiir kritis mana yang paling banyak muncul di masing-masing teks siswa program IPA dan IPS. Penelitian ini menggunakan metode deskriptif kualitatif, khususnya studi kasus. Subjek penelitian ini berjumlah 6 siswa yang dikategorian dalam tiga kelompok besar: high achiever, middle achiever, dan low achiever, dari program IPA dan IPS di salah satu SMA swasta di Kota Bandung. Instrumen penelitian yang digunakan untuk pengumpulan data yakni analisis teks siswa. Teks-teks siswa tersebut dianalisis melalui dua tahapan: pertama, dianalisis berdasarkan perspektif kebahasaan yang meliputi tujuan, struktur sematik, dan unsur kebahasaan dari teks eksposisi analitis; kemudian, dianilis dari perspektif berfikir kritis melalui teori berfikir kritis untuk mengetahui standar berfikir kritis yang paling banyak muncul pada elemen berfikir kritis dalam menulis teks eksposisi analitis di masing-masing program. Hasil penelitian menunjukkan bahwa perbedaan hasil tulisan siswa tidak dipengaruhi oleh perbedaan program studi, tetapi oleh perbedaan level pencapaian (rendah, sedang, tinggi). Lebih lanjut, penelitian ini juga mengindikasikan bahwa standar berfikir kritis yang paling banyak muncul di masing-masing program adalah: kejelasan (clarity) pada program IPA, serta kejelasan (clarity) dan relevansi (relevance) pada program IPS. Hasil tersebut, bagaimanapun, tidak mutlak karena hanya mewakili di ruang lingkup yang terbatas. oleh karena itu, penelitian-penelitian yang lebih komprehensif pada subjek sejenis sangat disarankan untuk dikalsanakan di masa yang akan datang. Kata kunci: berfikir kritis, menulis, teks eksposisi analitis, program IPA dan IPS.